FDI Flows to Asia : Did the Dragon Crowd Out the Tigers? - Mercereau, Benoit (IMF Working Papers; Working Paper ;, 2005)
China's dramatic success in attracting foreign direct investment (FDI) has raised concerns that it has success diverted FDI from other countries in Asia. We develop a new methodology to estimate crowding out, and we use it to investigate the impact of China's emergence on FDI flows to Asia using data from 14 Asian economies from 1984 to 2002. The results suggest that China did not have much impact on FDI to other countries. In particular, lowincome economies, which compete with China for low-wage investment, and countries with low levels of education or scientific development do not seem to have been especially affected.